Monitoring the hydration behavior of hardened cement paste affected by different environmental pH regimes - Zhu, Yu; Liu, Yijie; Zhang, Jinrui (Frontiers in Materials, 2022)
The purpose of this paper is to investigate the hydration behavior of hardened Portland cement paste cured in different environmental pH values by compressive strength, XRD, TG-DTG and EIS. Meanwhile, a newly proposed equivalent circuit model is built to establish the correlation between the electrochemical parameters and compressive strength of cement paste. The results show that the matrix strength, hydration products and pore structure of hardened cement paste are significantly affected by different pH values. According to the in-situ nondestructive monitoring of EIS, the evaluating for the matrix strength of cement-based materials can be achieved by calculating the resistivity of discontinuous connected pores (Rcp) in the recommended equivalent circuit model.